Peran Pendidik dalam Membentuk Moral Panti Asuhan:: Efektivitas dan Tantangan dalam Pembentukan Karakter Anak Asuh - Syafirah Azra Wiguna; Safrina Zahfira Siregar; M. Umar Saifurrahman Zaidan; Shakila Najifah Putri Lubis; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
This article discusses the important role of educators in shaping moral values in orphanages and the significant implications they have for the character development of foster children. In the context of orphanages, educators play a key role in helping foster children develop strong moral values and build positive character. Apart from providing basic needs and formal education, education in orphanages has an important role in shaping the character and morals of foster children. Caregivers in orphanages have a responsibility to provide good moral guidance and create a supportive environment in efforts to build the character and morals of these children. Based on the results of research conducted at the Rumah Kasih Bakti Anak Indonesia Foundation, the methods used by social workers at the orphanage are in accordance with the methods commonly used by social workers. Thus, this article presents an understanding of the important role of educators in shaping moral values in orphanages and describes the methods used in building the character and morals of foster children.